Role of Vitamin D in Vascular Complications and Vascular Access Outcome in Patients with Chronic Kidney Disease - Santoro, Domenico; Pellicanò, Vincenzo; Cernaro, Valeria; Lacava, Viviana; Lacquaniti, Antonio; Atteritano, Marco; Buemi, Michele (Current Medicinal Chemistry, 2016)
Vitamin D has been known for a long time as a major factor involved in the calcium- phosphate balance and homeostasis, along with parathyroid hormone (PTH). While vitamin D effects on calcium and phosphate are fully known, recent studies attempted to link vitamin D status and cardiovascular diseases. The involvement of vitamin D on vascular remodeling is mediated by several mechanisms such as activation of renin-angiotensin-aldosterone system (RAAS), cell proliferation and anti-apoptotic cell pathways. This correlation is highlighted by the fact that the activated form of vitamin D (1,25 (OH)2 D3) can be synthesized by the same endothelial cells, due to the constitutive presence of endothelial 1α-hydroxylase. Vitamin D reduces the expression of angiotensin 2 receptor (AT2R) on the endothelial cell surface (AT2R), leading to a cascade of events that result in the synthesis of vasodilators, such as nitric oxide. The activation of vitamin D receptors (VDRs) on endothelial cells induces changes in the metabolic activity of the endothelium and is responsible for cell survival, proliferation and neoangiogenesis. Moreover, altered signaling of VDR due to gene polymorphisms has been demonstrated in patients with cardiac disorders and chronic kidney disease (CKD). Recently, vascular access outcome has been associated with vitamin D status. Future studies will help to better define the need of vitamin D supplementation for a better cardiovascular as well as vascular access outcome in patients with CKD.
Keywords: vitamin D